Pendampingan dan Pengembangan Pembibitan Kelapa Sawit Tahap Pre Nursery - Pebrianto, Rosihan; Yusuf, Maulana; Ibrahim, Eddy (Prima Abdika: Jurnal Pengabdian Masyarakat, 2023)
Oil palm is one of the main plantation commodities in the South Sumatra region. The high price of palm oil makes people try to open or replace their land into oil palm plantations. The failure of the people's oil palm nurseries is a very serious problem during the pandemic. However, in preparing the oil palm seeds, the community is considered a failure because the success rate for the nursery is below 50% or even only 20%. The community's ability to buy oil palm seeds also does not exist because the seeds sold in the market range from Rp. 23,000 to Rp. 45,000 per seed 6 months old. Therefore, assistance and development of early stage oil palm nurseries is carried out. It is hoped that this activity can help the community's difficulties in an effort to participate in the welfare of the local community. The method used is the delivery of material then followed by practice. This practice starts from preparing the planting medium, planting, care, and maintenance. The results obtained show that the failure of the nursery experienced by the community was caused by an inappropriate planting medium, namely the size of a polybag less than 30cm x 30 cm. Then there is no shade so that many seeds experience drought and die. Maintenance of seeds that are not given enough attention, such as watering and fertilizing. These three factors are the main problem of nursery failure. The results of the nursery carried out in this activity reached 98% of the total seeds planted.